Separating mind and body: an approach to the thoughts and feelings of female university students/sexual workers - Martha Catalina Loaiza G; Lina Yésica Moreno O; Eliana Zuluaga P (Universidad de Antioquia, 2007)
This article takes into account the vision of female university students who are also sexual workers and the meaning that job has for them. Objective: to understand the meaning that sexual job has for female university students/sexual workers, what they think and feel about it. Methodology:qualitative research was the starting point using ethnographical techniques such as the interview, the ﬁeld diary and documental revision. Results: the daily life of female university students/sexual workers goes around their family, university and work, where they separate mind from body as a mechanism of emotional protection to avoid sadness and deception.